Stingless bees honeys': physical-chemical characterization, difficulties and challenges (Research, Society and Development, 2022)
Stingless bees form a group of eusocial bees belonging to the tribe Meliponini (Hymenoptera: Apidae) and are distributed in tropical and subtropical regions of the planet. Brazil, the main territory regarding stingless bees’ diversity, has a large variety of phytogeographic regions that can influence the physical-chemical properties of the honey. Currently, the country does not have a legislation that represents its territorial reality as a whole, making the parameters unattainable for producers to market stingless bees’ honey. In addition to its economic importance for producers, this product has sensory characteristics that are different from those produced by Apis mellifera, making it a product with high added value. Additionally, honey production is a sustainable practice and increases bee conservation, which, in general, are mainly threatened by human interference. Thus, the objective of this work was to analyze the scientific productions published in consolidated databases to understand how bees deal with different environmental and geographic conditions and how this reflects on honey characteristics, in addition, to generate data to prepare a proposal to standardize and market the honey. For this, the StART software was used, with the elaboration of a systematic review protocol. A total of 93 articles were listed in the initial search in the Web of Science, Scopus and Google Scholar databases and after the selection and execution process, 50 articles were selected. In the summarization phase, it was observed that there is still no consensus among researchers on how to stipulate a standard and reference ranges for the analyses.